Associations between class-level factors and student physical activity during physical education lessons in China - Yulan Zhou; Lijuan Wang; Ruzhuan Chen; Bingnan Wang (International Journal of Behavioral Nutrition and Physical Activity)
Abstract Background The purpose of this study is to explore the association between class-level factors, such as lesson start time, class size, lesson location, PE content, and PE context, and student engagement in moderate-to-vigorous physical activity (MVPA) during PE lessons in both elementary and middle schools. Methods A total of 284 PE lessons from ten schools in Shanghai, Eastern China, were included in the study. Students’ MVPA during PE lessons was recorded using accelerometry, and lesson context was evaluated using the System for Observing Fitness Instruction Time (SOFIT). Mixed linear regression analysis was applied to assess the association between class-level factors and MVPA during elementary and middle school PE lessons. Results Students in elementary school spent 40.3 ± 8.1% of PE lesson time in MVPA, while middle school students spent 40.5 ± 7.1%. Significant relationships were found between MVPA and class-level factors like lesson location, PE content, and PE context. Specifically, elementary school students recorded a higher percentage of MVPA during lessons with team games, individual games, individual activities, and more time spent on skill practice and game play context. In middle schools, higher MVPA was connected to outdoor lessons, a focus on individual games, and more time devoted to fitness context. Conclusions Class-level factors may affect students’ MVPA differently depending on the school level, and these modifiable factors should be targeted to increase MVPA time in elementary and middle school PE classes. Future studies should investigate ways to modify these factors, strategically plan lesson time across different contexts, and optimizing PE content to boost MVPA in PE lessons.